2018
DOI: 10.1016/j.devcel.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Rab-Effector-Kinase Interplay Modulates Intralumenal Fragment Formation during Vacuole Fusion

Abstract: Upon vacuolar lysosome (or vacuole) fusion in S. cerevisiae, a portion of membrane is internalized and catabolized. Formation of this intralumenal fragment (ILF) is important for organelle protein and lipid homeostasis and remodeling. But how ILF formation is optimized for membrane turnover is not understood. Here, we show that fewer ILFs form when the interaction between the Rab-GTPase Ypt7 and its effector Vps41 (a subunit of the tethering complex HOPS) is interrupted by a point mutation (Ypt7-D44N). Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 96 publications
(176 reference statements)
2
27
0
Order By: Relevance
“…2D), and also no major time delay between lipid mixing and content mixing ( Fig. 2E), indicative of normal pore formation kinetics (Karim et al, 2018). Together, these results show C26 VLCFAs positively regulate homotypic vacuole fusion, evidenced by morphological changes in live cells, and a significant reduction in the measurable in vitro lipid-and content mixing of isolated vacuoles.…”
Section: Yeast Without Elo3p Have Misshapen Vacuoles and Are Deficiensupporting
confidence: 51%
See 4 more Smart Citations
“…2D), and also no major time delay between lipid mixing and content mixing ( Fig. 2E), indicative of normal pore formation kinetics (Karim et al, 2018). Together, these results show C26 VLCFAs positively regulate homotypic vacuole fusion, evidenced by morphological changes in live cells, and a significant reduction in the measurable in vitro lipid-and content mixing of isolated vacuoles.…”
Section: Yeast Without Elo3p Have Misshapen Vacuoles and Are Deficiensupporting
confidence: 51%
“…However, it should be noted that other studies have demonstrated an activation of the V-ATPase upon the addition of exogenous, shortchain PtdIns(3,5)P2 and a stabilization of the VO-V1 complex by this lipid, suggestive of a protein-lipid interaction (Li et al, 2014). There has recently been significant work in uncovering the mechanism and function of the formation of intralumenal fragments (ILFs) following homotypic vacuolar fusion (Karim et al, 2018;Mattie et al, 2017;McNally et al, 2017). The formation and visualization of ILFs is possible when stalk expansion and pore formation takes place very quickly following the formation of the hemifusion diaphragm, and when the rate of hemifusion is slowed down, the ILFs do not form.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations